Pricing of IPO for Internet companies. - Lim, Danny. (2008)
This paper examines the factors that affected the pricing of IPO of Internet firms. The factors that will be covered are 1) Role and reputation of Underwriters, 2) Timing of the Issue, 3) Venture Capital, 4) Revenue and Expenses and 5) Information Asymmetry.